Pengaruh Mastery Experience Dan Verbal Persuasion Terhadap Self Efficacy Peserta Didik Di MTsN 10 Agam - Syawaluddin; Arjoni; Khofifah Makhmuuda; Yeni Afrida (Universitas Veteran Bangun Nusantara, 2025)
This study is motivated by the phenomenon of low self-efficacy among some students at MTsN 10 Agam. Several students demonstrated pessimism, hesitation, low confidence, and a tendency to avoid active participation in learning activities. Self-efficacy defined as the belief in one’s own ability to accomplish tasks is a crucial factor in academic success and is influenced by factors such as mastery experience and verbal persuasion. This research aims to determine the effect of these two variables on students’ self-efficacy. Using a quantitative approach with an associative research design, a sample of 165 students was selected from a population of 281. Data were collected using a Likert-scale questionnaire and analyzed using simple and multiple linear regression with SPSS 26. The results showed that mastery experience had a significant effect on self-efficacy, contributing 79.5%, while verbal persuasion contributed 29.9%. Simultaneously, both variables accounted for 80% of the variance in students’ self-efficacy. These findings highlight the importance of successful personal experiences and constructive verbal support in enhancing students' confidence in learning contexts.